Anatomical Features of the Interscapular Area Where Wet Cupping Therapy Is Done and Its Possible Relation to Acupuncture Meridians - Roshanak Ghods; Nasrin Sayfouri; Mohammad Hossein Ayati (Medical Association of Pharmacopuncture Institute, 2016)
Although wet cupping has been a treatment for centuries, its mechanism of action is not well understood. Because the anatomical features of the wet-cupping area might play a role in its mechanism, we focus on the features of the interscapular area in which a common type of wet-cupping therapy (WCT), called Hijamat-e-Aam in Iranian medicine, is usually applied and discuss the possible relation of those features to the acupuncture meridians. We gathered and analyzed data from reliable textbooks on modern medicine with a focus on the anatomical features of the interscapular area, topics related to WTC in Iranian medicine, and acupuncture sources obtained by searching PubMed, Google-Scholar, and Science Direct. The interscapular area used for WCT was found to have special features: brown adipose tissue, immediate proximity to sympathetic ganglia, passage of the thoracic duct, two important acupuncture meridians, and proximity to the main vessel divisions carrying blood from the heart and the brain. These features indicate that the interscapular application of WCT not only discharges waste materials through a shifting of blood to the site after application of a traction force but also invigorates the body's metabolism, increases immunity, and regulates blood biochemistry, which are desired therapeutic effects of WCT.